Privacy Protection - Emerging Issues and Technological Responses - Gupta, Ayush; Gupta, Manvi (International Journal of Computer Sciences and Engineering, 2021)
Privacy protection as a process of collection, processing and dissemination of Information is a burgeoning issue that is challenging researchers, scientists and regulators. A universal ethical concern of the organizations, individuals and society at large is how the Information is accessed and manipulated. Technology creates implications for the privacy of people in a variety of areas, and privacy Issues appear at a variety of platforms calling for the formation of standards and regulations. The regulations are still evolving and are not optimal since the technological contexts are highly dynamic. Our paper presents the privacy trends, regulation of privacy in some standard frameworks, technological contexts and emerging ethical considerations. We also highlight the ethical issues with privacy protection and motivates to develop new methodologies to handle privacy from a both legal and technological perspective. The technological context and legal framework go together for the protection of privacy. However, privacy issues are complex and will continue to evolve. People have to find the best ways of handling ethical issues in specific situations. Researches on the protection of privacy in various computing environments may be carried out given a specific technology environment that can in customizing for region-specific legislation.